Quaternary volcanic evolution in the continental back-arc of southern Mendoza, Argentina. (July 2018) - May, Venera R.; Chivas, Allan R.; Dosseto, Anthony; Honda, Masahiko; Matchan, Erin L.; Phillips, David; Price, David M.
Abstract: The Payenia Basaltic Province (PBP) is the largest and the northernmost of the Quaternary back-arc Patagonian basaltic provinces in South America. In the last 10 years, several studies have investigated either, the geochemistry or the geochronology of this basaltic province. However, only a few investigations have focused on the two aspects simultaneously in order to reconstruct its Quaternary volcanic history. Consequently, this study aims to provide new Quaternary ages and to contribute in understanding how its geochemistry evolved though time. In the current study nine basaltic flows from the PBP in central west Argentina were dated using a combination of cosmogenic surface exposure, 40 Ar/ 39 Ar, and thermoluminescence dating methods. Seven flows have Middle to Late Pleistocene ages and two erupted in the Holocene. Using the new ages here inferred and the previously published Quaternary geochronology, together with the available geochemical data, maps of Pleistocene geochemical evolution have been generated. These maps indicate that two geochemically distinct magma types erupted over the same time interval (ca. 1.5 Ma) within the PBP: In the north-eastern part (Nevado volcanic field) of the province, an arc-like signature is distinguishable, whereas the southern part of the PBP (Río Colorado volcanic field) exhibits an intraplate, Ocean Island Basalt (OIB)-like signature. The arc-like signature decreases in the Early to Middle Pleistocene as indicated by a reduction in Ba/La and La/Ta values in the Nevado volcanic field. At ca. 0.25 Ma a similar disparity has been inferred between two volcanic fields on the western part of the PBP, one erupting lavas with arc-like characteristics and the other with OIB-like signatures, despite being only tens of kilometres apart. Holocene volcanism is restricted to the western side of the Payún Matrú volcanic field and is dominated by OIB-like signatures, notably high Ta/Hf and low Ba/La and La/Ta values. Graphical abstract: Image 1 Highlights: Seven new ages have been acquired for the Payenia Basaltic Province (PBP). Three different dating methods have been employed for the dating. At ∼0.25 Ma two volcanic fields erupted basalt with different geochemical signatures. The PBP had its volcanic activity peak during the Middle to Late Pleistocene'. The PBP was last active ∼5ka in a restricted area with OIB-like signatures.